Unlawful Acts (Onrechtmatigedaad) regarding Land Ownership Disputes (Study of Marisa District Court Decision Number: 11/Pdt.G/2019/PN.Mar) - Awalulkhairi Santosa Putra; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2023)
In cases regarding land, they are often related to civil cases which fall into the field of unlawful acts (Onrechtmatigedaad), Article 1365 of the Civil Code (KUHPer). Looking at the decision regarding unlawful acts in the case of land disputes based on the Marisa Court Decision Number: 11/Pdt.G/2019/PN Mar, the Marisa District Court judge decided that the Defendant had committed an Unlawful Act against the land rights owned by the Plaintiff.This research uses a juridical normative approach whose main data source is secondary data, namelylegal norms contained in statutory regulations and court decisions as well as legal norms that exist in society. From this research, the results obtained are thatThe author describes the elements of each unlawful act in Article 1365 of the Civil Code from case number: 11/Pdt.G/2019/PN.Mar. So it is true that the Defendant has fulfilled all the elements in committing an unlawful act. That according to the Panel of Judges in its legal considerationsA private sale and purchase agreement regarding land rights is valid and has binding legal force as long as the agreement is carried out clearly and in cash and is witnessed and acknowledged by the Village. So that the ownership of the plaintiff's land rights legally belongs to him.